Pengembangan Media Video Pembelajaran Menggunakan Aplikasi Canva Pada Materi Spltv Kelas X SMA Wisuda Pontianak - arifin, krisman; Oktaviana, Dwi; Haryadi, Rahman (LPD IKIP PGRI Pontianak, 2024)
This research aims to develop learning video media using the Canva application on SPLTV class X SMA Wisuda Pontianak material that is valid, practical and effective. This research is research that refers to a 4D design model that was modified into 3D, namely the definition stage, the design stage and the development stage. The instruments used are validation sheets, questionnaires and posttests. Questionnaires are used for expert validation, teacher and student responses, and posttest questions. This research produced learning videos with a validity level of 84.24% with very valid criteria, teacher and student response questionnaire results with an average of 92.12% were very practical, and student posttest results were 80% with effective criteria